Detection of Organochlorine Pesticide (OCPs) Residues and Trace Metals in Some Selected Malt Drinks in Nigeria - Godwin O. Olutona; Sophia Toluwalogo Livingstone (Beverages, 2018)
In this study we evaluated the trace metals and toxic residues of pesticides in commercial malta drinks sold in Nigeria markets. Residual concentrations of seventeen (17) chlorinated hydrocarbons and trace metals were determined in fifteen samples of three batches each of five selected brands of Malta drink sold in Nigeria markets. Gas Chromatograph-Electron Capture Detector (GC-ECD) and Atomic Absorption Spectrophotometry (AAS) were employed in quantitative analysis. The results revealed that all the malt drink analyzed have one or more OCPs detected. The presence of eleven (11) OCPs residue were detected at varying concentrations. The total burden of OCPs in the samples was in the following order: AMS > DUB > MAG > HIM > MLT. Trace metals results revealed that Cd was below detection limit in all the samples while Pb; Ni and Cr were above World Health Organization and United State Environmental Protection Agency (WHO/USEPA) limits for drinking water.